Being Content Creator to Improve Students' Self-confidence in Speaking English - Ida Dian Sukmawati; Tri Pujiani; Neilia Almustaflikhah (LPPM Universitas Harapan Bangsa, 2022)
People are said to master English if they can speak English fluently. However, speaking is a complex activity requiring many other skills such as vocabulary, pronunciation, grammar, and so on. Thus, most students feel that speaking is the most difficult skill. Self-confidence is one of the factors that influencing speaking performance. The students’ self-confidence can be stimulated by using an interesting activity, such as being an educative content creator. This research was a case study conducted at Fun English Club of Harapan Bangsa University having a project of developing a YouTube channel by utilizing its members as the content creator. This study aimed to find out how being content creator can improve the students’ self-confidence in speaking English. The study was conducted by observing the implementation of this project, distributing questionnaire and interviewing some members. The result showed that the students felt more confident in speaking English after joining the project. Therefore, it can be concluded that being content creator increases the students’ self-confidence in speaking English. This project should be continued and developed to maintain the students’ self-confidence and facilitate more practice for students in speaking English.